CEO/CFO turnover and subsequent remediation of information technology material weaknesses. (20th September 2017) - Li, Wanyun; Phang, Soon‐Yeow; Ho, Shuk Ying
Abstract: Adding to prior research on internal control material weaknesses (ICMW), our study investigates whether information technology material weaknesses (ITMWs) are associated with CEO/CFO turnover, and whether their turnover will promote subsequent remediation. We find that disclosures of ITMW are positively associated with CEO/CFO turnover; however, only CEO turnover promotes subsequent remediation. Our findings on ITMW are different from the prior findings on ICMW – aligned with prior research on ICMW, ITMWs are associated with CEO/CFO turnover; however, unlike prior research on ICMW suggests, dismissals of CFOs do not promote subsequent remediation of ITMW. Thus, future research should consider ICMW and ITMW separately in the examination of their consequences and remediation.